2016
DOI: 10.1155/2016/3670951
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Sleep Spindle Characteristics and Sigma Power across Early Childhood

Abstract: Sleep spindles, a prominent feature of the non-rapid eye movement (NREM) sleep electroencephalogram (EEG), are linked to cognitive abilities. Early childhood is a time of rapid cognitive and neurophysiological maturation; however, little is known about developmental changes in sleep spindles. In this study, we longitudinally examined trajectories of multiple sleep spindle characteristics (i.e., spindle duration, frequency, integrated spindle amplitude, and density) and power in the sigma frequency range (10–16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 45 publications
7
37
1
Order By: Relevance
“…11 On the other hand, a longitudinal study of 8 children showed a decrease in spindle frequency and no change in spindle density between ages 2-3 and 5. 12 This study also showed that spindle duration, amplitude and sigma power selective to the slow spindle range (11.25-13.00 Hz) all increased with age. Similarly, a small cross-sectional study of children aged 0-4 years revealed an increase in slow spindle density with age and a negative correlation between mean spindle frequency and age.…”
Section: Introductionsupporting
confidence: 58%
“…11 On the other hand, a longitudinal study of 8 children showed a decrease in spindle frequency and no change in spindle density between ages 2-3 and 5. 12 This study also showed that spindle duration, amplitude and sigma power selective to the slow spindle range (11.25-13.00 Hz) all increased with age. Similarly, a small cross-sectional study of children aged 0-4 years revealed an increase in slow spindle density with age and a negative correlation between mean spindle frequency and age.…”
Section: Introductionsupporting
confidence: 58%
“…Normally, REM% decreases through infancy; a comparison of 2- and 5-year olds found reductions in both REM minutes (175–140) and REM% (29–24%) (171). This REM decrease may be accelerated by early adversity.…”
Section: The Stress Acceleration Hypothesis Of Nightmaresmentioning
confidence: 99%
“…In a study of sleep spindles in children from 2-5 years of age, it was found that spindle duration, amplitude, and power increased with age, whereas mean spindle frequency decreased. 102 Importantly, there was no change in spindle density with increasing age (Fig. 3).…”
Section: Neurophysiological Evidence-eegmentioning
confidence: 91%
“…Even earlier, by age 6–8 months, there is a well‐formed, symmetric, and synchronous sleep architecture identical to that found in adults. In a study of sleep spindles in children from 2–5 years of age, it was found that spindle duration, amplitude, and power increased with age, whereas mean spindle frequency decreased . Importantly, there was no change in spindle density with increasing age (Fig.…”
Section: Clinical Evidence Supporting Extrapolation Of Aed Efficacy Imentioning
confidence: 95%
See 1 more Smart Citation